Student Perceptions of The E-Learning Program Based on Learning Management System (LMS) on Akhlak Akidah Materials - Dea Tara Nintgyas (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2021)
E-Learning has a great influence on the learning process. The implementation of e-learning not only answers the challenges of the times but also becomes a solution for sustainable learning during the pandemic. The study aims to look at student perceptions of the implementations of LMS (Learning Management System) based e-learning on morals learning material for the PGMI IAIN Metro study program. Collecting data in this study used a questionnaire in the form of an attitude scale to find data on students' perceptions of LMS -based e-learning programs and students' perceptions of aqidah akhlak material. These two variables are supported by 5 indicators with 20 statements and analyzed using descriptive statistics to calculate the percentage of each indicator. The results showed that the LMS-based e-learning program could make the learning process easy, creative, independent and increase students' understanding of the moral aqidah material. Although it is less effective to use due to unstable signal coverage in certain areas. Therefore, the provision of facilities and infrastructure is needed to support internet access in remote areas.